Multicultural Strategies for Community Colleges Expanding Faculty Diversity - Kirkpatrick, Laura; ERIC Clearinghouse for Community Colleges (Los Angeles, CA : ERIC Clearinghouse for Community Colleges, 2001)
This digest explores the community college's mission to increase student attendance and performance by improving faculty diversity. Community colleges are filled with multicultural, diverse students who bring different knowledge and skills to educational institutions. These students are also attracted to the community college for different reasons. The faculty/student relationship is seen as the core to the learning experience. Students have to be able to identify with the faculty, and faculty members have to be able to identify with the students. A diverse student body needs instruction and leadership from a diverse faculty and administration. Case studies include five community colleges from different regions of the country that are increasing diversity through: (1) focused recruitment of underrepresented groups; (2) internships for individuals from diverse backgrounds, which help impart knowledge on overall community college instruction and operation; (3) fellowships; (4) transfer agreements with historically black colleges; (5) diverse faculty/staff mentor programs, which provide information to future administrators and faculty; and (6) professional development (national organization workshops/conferences). The digest concludes that the global expansion of education makes diversity necessary to community college survival and achievement. (Contains 11 references.) (MKF)
Availability: ERIC Clearinghouse for Community Colleges. University of California at Los Angeles, 3051 Moore Hall, P.O. Box 951521, Los Angeles, CA 90095-1524. Tel: 310-825-3931. For full text: http://www.gseis.ucla.edu/ERIC/eric.html.
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: ED-99-CO-0010.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Colleges; Diversity (Faculty); Multicultural Education; Student Characteristics; Teacher Characteristics; Teacher Student Relationship; Two Year College Students; Two Year Colleges; ERIC Digests; ERIC Publications; ERIC Digests in Full Text